Interleukin-6, CXCL10 and Infiltrating Macrophages in COVID-19-Related Cytokine Storm: Not One for All But All for One! - Coperchini, Francesca; Chiovato, Luca; Rotondi, Mario (Frontiers in Immunology, 2021)
Abstract SARS-COV-2 virus is responsible for the ongoing devastating pandemic. Since the early phase of the pandemic, the “cytokine-storm” appeared a peculiar aspect of SARS-COV-2 infection which, at least in the severe cases, is responsible for respiratory treat damage and subsequent multi-organ failure. The efforts made in the last few months elucidated that the cytokine-storm results from a complex network involving cytokines/chemokines/infiltrating-immune-cells which orchestrate the aberrant immune response in COVID-19. Clinical and experimental studies aimed at depicting a potential “immune signature” of SARS-COV-2, identified three main “actors”, namely the cytokine IL-6, the chemokine CXCL10 and the infiltrating immune cell type macrophages. Although other cytokines, chemokines and infiltrating immune cells are deeply involved and their role should not be neglected, based on currently available data, IL-6, CXCL10 and infiltrating macrophages could be considered prototype factors representing each component of the immune system. It rapidly became clear that a strong and continuous interplay among the three components of the immune response is mandatory in order to produce a severe clinical course of the disease. Indeed, while IL-6, CXCL10 and macrophages alone would not be able to fully drive the onset and maintenance of the cytokine-storm, the establishment of a IL-6/CXCL10/macrophages axis is crucial in driving the sequence of events characterizing this condition. The present review is specifically aimed at overviewing current evidences provided by both in vitro and in vivo studies addressing the issue of the interplay among IL-6, CXCL10 and macrophages in the onset and progression of cytokine storm.